2018
DOI: 10.23902/trkjnat.369911
|View full text |Cite
|
Sign up to set email alerts
|

SCREENING FOR ANTI-QUORUM SENSING AND ANTI-BIOFILM ACTIVITY IN Viscum album L. EXTRACTS AND ITS BIOCHEMICAL COMPOSITION

Abstract: Many opportunistic pathogenic bacteria use the Quorum Sensing (QS) system to coordinate their virulence expressions. Thus, QS can likely be a new approach to control bacterial infections. The aim of this study was to evaluate the antimicrobial, anti-biofilm, and anti-quorum sensing activities of ethanol, chloroform, and dichloromethane: methanol extracts of leaf, stem, and fruits of the European mistletoe Viscum album L. on 2 Gram-positive and 7 Gram-negative pathogenic bacteria. The extracts at concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Several factors, including the polarity of extraction solvents, extraction methods, target bacteria used in each study, and types of phytochemical constituents contained in H. tiliaceus plant parts, might have been associated with this heterogeneity in the MIC values of H. tiliaceus among studies (Mostafa et al 2018). However, similar MICs (10, 8-10, and 150 mg/mL) as those obtained in the present study have been reported in several previous investigations for ethanol leaf extract of Moringa oleifera against C. violaceum , ethanol extracts of various plant species against S. aureus (Bussmann et al 2010), and ethanol and chloroform leaf and stem extracts of Viscum album L. against various strains of P. aeruginosa (Erdönmez et al 2018), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Several factors, including the polarity of extraction solvents, extraction methods, target bacteria used in each study, and types of phytochemical constituents contained in H. tiliaceus plant parts, might have been associated with this heterogeneity in the MIC values of H. tiliaceus among studies (Mostafa et al 2018). However, similar MICs (10, 8-10, and 150 mg/mL) as those obtained in the present study have been reported in several previous investigations for ethanol leaf extract of Moringa oleifera against C. violaceum , ethanol extracts of various plant species against S. aureus (Bussmann et al 2010), and ethanol and chloroform leaf and stem extracts of Viscum album L. against various strains of P. aeruginosa (Erdönmez et al 2018), respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Further, oleanolic acid (OA), a potent drug used clinically as an anti-inflammatory agent (Zheng et al, 2015), is the only indicator. In terms of bioactivity, alcohol extracts of the plant or related species also possess some antibacterial, antioxidant, antiinflammatory, and anticancer activities (Chamlagai & Singh, 2016;de Oliveira Melo et al, 2018;Erdönmez et al, 2018;Garg et al, 2013;Holandino et al, 2020;Nag et al, 2016;Stefanucci et al, 2020;, whereas water extracts are considered to possess antioxidant, hypoglycemic, and lipidlowering activity (Mishra et al, 2018;. However, the specific active ingredients are not yet known.…”
mentioning
confidence: 99%
“…Biofilm formation is a major problem factor in many areas, ranging from industrial corrosion and biofouling to chronic and nosocomial infections [25]. Indeed, many strains of uropathogens can form a biofilm (physical barrier against antimicrobial agents) allowing them to avoid the immune system and increase their resistance to recommended drugs [26] [27]. The results of this study showed that the extracts resulted in the formation of biofilm on the resistant strains used (Figure 3 and Figure 4).…”
Section: Discussionmentioning
confidence: 89%
“…The results of this study showed that the extracts resulted in the formation of biofilm on the resistant strains used (Figure 3 and Figure 4). The eradication of biofilms is of great importance in the fight against infection [27]. The ability to inhibit the biofilm of E. coli by the ethanolic extract of the leaves of Carica papaya over a range of concentrations was shown in the study conducted by Hastuty [28].…”
Section: Discussionmentioning
confidence: 99%